A Quantitative Study of Gully Erosion Based on Object-Oriented Analysis Techniques: A Case Study in Beiyanzikou Catchment of Qixia, Shandong, China. (29th January 2014) - Wang, Tao; He, Fuhong; Zhang, Anding; Gu, Lijuan; Wen, Yangmao; Jiang, Weiguo; Shao, Hongbo
Abstract : This paper took a subregion in a small watershed gully system at Beiyanzikou catchment of Qixia, China, as a study and, using object-orientated image analysis (OBIA), extracted shoulder line of gullies from high spatial resolution digital orthophoto map (DOM) aerial photographs. Next, it proposed an accuracy assessment method based on the adjacent distance between the boundary classified by remote sensing and points measured by RTK-GPS along the shoulder line of gullies. Finally, the original surface was fitted using linear regression in accordance with the elevation of two extracted edges of experimental gullies, named Gully 1 and Gully 2, and the erosion volume was calculated. The results indicate that OBIA can effectively extract information of gullies; average range difference between points field measured along the edge of gullies and classified boundary is 0.3166 m, with variance of 0.2116 m. The erosion area and volume of two gullies are 2141.6250 m 2, 5074.1790 m 3 and 1316.1250 m 2, 1591.5784 m 3, respectively. The results of the study provide a new method for the quantitative study of small gully erosion.